Razvoj prostorske metode določanja obmestnih krajin - Žlender, Vita (Urbani izziv, 2021)
The ill-defined space between urban and rural areas is typically referred to as peri-urban landscape. One key reason for this lack of clarity is the unduly broad scale of conceptual and geographical resolution. This article focuses on its spatial elucidation at a sub-regional scale. It describes a method for delineating peri-urban landscape, based on spatial and demographic criteria. Arguably, spatially explicitly denoted peri-urban landscape on a sub-regional level would help in choosing appropriate local and region al planning approaches and policies for its development. The method, based on an overlay analysis, was tested using datasets from regional and municipal authorities in Ljubljana and Edinburgh. The results indicate that this less ambiguous spatial definition of peri-urban landscape offers a sound basis for planning and policy development.
Keywords: Edinburg; GIS; krajinsko načrtovanje; landscape planning; Ljubljana; metoda prekrivanja; obmestna krajina; overlay method; peri-urban landscape